The Impact of Economic Aid on Climate Change Mitigation in Uganda - Hajara Mirembe (Uganda Christian University, 2024)
The interplay between economic aid and climate change mitigation is a critical area of study, particularly in developing nations like Uganda, where environmental vulnerabilities are pronounced. This research contributes to the understanding of how economic aid can be leveraged for effective climate change mitigation in Uganda. It underscores the importance of aligning financial support with local needs and capacities to foster sustainable development outcomes. It employs a mixed-methods approach, combining quantitative data analysis of economic aid flows to Uganda with qualitative interviews from stakeholders involved in climate initiatives. The analysis covers various forms of aid, including bilateral and multilateral assistance, and examines their correlation with climate-related outcomes such as emissions reductions and adoption of renewable energy sources. Preliminary findings suggest that while economic aid has the potential to bolster climate change mitigation efforts, its impact is contingent upon several factors, including governance structures, local capacity for implementation, and alignment with national priorities. Specific case studies highlight successful projects funded by international donors that have led to significant improvements in environmental sustainability. The results indicate that targeted economic aid can enhance Uganda’s ability to address climate challenges effectively. However, there are also instances where poorly coordinated aid efforts have resulted in limited impact or even adverse effects on local ecosystems. The study emphasizes the need for strategic planning and collaboration among stakeholders to maximize the benefits of economic assistance.
Undergraduate Research